Pre-Service English Teacher’s Experiences in Using Pedagogical Code-Switching in EFL Classroom: A Narrative Inquiry Study - Annisa Putri Dwi Marsa Sadjat; Andrie Chaerul; Mansyur Srisudarso (Edumaspul: Jurnal Pendidikan, 2021)
This research focuses on the experience of pre-service teachers who are carrying out teaching and learning practices in 8th grade Senior High Schools. By using code-switching to explain English subject matter at the school, as well as solving a problem during teaching and learning. For example, 1. How is Indonesian pre-service teachers' code switching functioned in EFL classes? 2. How did the use of code-switching as a teaching strategy influence the respect the Grade 8 Natural Sciences students had for their teacher?